Selective retina therapy with real-time feedback-controlled technology in central serous chorioretinopathy: a 24-month follow-up real-world prospective study - Hyeong Gon Yu; Chang Ki Yoon (BMJ Open Ophthalmology, 2024)
Objective Although central serous chorioretinopathy (CSC) treatment using selective retinal therapy (SRT) has presented favourable outcomes, no long-term studies with a real-world clinical practice regimen have been conducted.Methods and analysis We performed a long-term assessment of CSC treatment using SRT with real-time feedback (RTF) technology. 50 patients (53 eyes) with CSC and more than a 1-month symptom duration were recruited and treated with SRT using a 1.7 µs pulse width, 527 nm neodymium-doped yttrium lithium fluoride (Nd:YLF) laser equipped with an RTF system.Results After 6 months of treatment, complete subretinal fluid resolution was achieved in 62% of the eyes. The mean best-corrected visual acuity (BCVA; logarithm of the minimum angle of resolution, mean±SD) improved slightly from 0.15±0.18 at baseline to 0.12±0.21 at 6 months (p=0.062). The central retinal thickness (CRT; mean±SD) was reduced significantly from 350.6±100.1 µm at baseline to 268.2±70.6 µm at 6 months (p<0.001). Long-term follow-up revealed significant improvements in BCVA, from 9 months until 24 months, and in CRT, from 1 month until 24 months. No treatment-related adverse events were observed during the 24-month follow-up period.Conclusion Our results suggest that SRT with RTF technology is a long-term safe treatment with anatomical improvement for patients with CSC.